CLASSROOM MANAGEMENT IN AN INTENSIVE ENVIRONMENT - Safarova Dildora; Qo'ziboyeva Kumush; Raxmatova Visola; Yaxshiboyeva Ma'mura (TADQIQOTLAR, 2025)
Annotation This  article  explores  effective  classroom  management  strategies  tailored  to intensive learning environments, where time is condensed and student engagement is critical.  Intensive  programs  pose  unique  challenges  such  as  accelerated  content delivery, high student anxiety, and increased teacher workload. Effective management includes  clear  routines,  active  engagement,  differentiated  instruction,  and  ongoing feedback.  Emphasis  is  placed  on  building  a  positive  classroom  culture,  setting expectations, and using technology to streamline instruction. This article serves as a guide for teachers and administrators working in language centers, summer schools, or accelerated university programs.